Improving the reproductive health of married and unmarried youth in India : evidence of effectiveness and costs from community-based interventions : final report of the Adolescent Reproductive Health Program in India - Pande, Rohini (Rohini P.) (ICRW, 2006)
Collaborative program of ICRW with various Indian agencies.